Anti-glutathione S-transferase theta 1 antibodies correlate with graft loss in non-sensitized pediatric kidney recipients - Comoli, Patrizia; Cioni, Michela; Ray, Bryan; Tagliamacco, Augusto; Innocente, Annalisa; Caridi, Gianluca; Bruschi, Maurizio; Hariharan, Jayasree; Fontana, Iris; Trivelli, Antonella; Magnasco, Alberto; Nocco, Angela; et al. (Frontiers in Medicine, 2022)
Immunity to HLA antigens cannot explain all cases of ABMR, nor the differences observed in the outcome of kidney recipients with circulating DSAs endowed with similar biologic characteristics. Thus, increasing attention has recently been focused on the role of immunity to non-HLA antigenic targets. We analyzed humoral auto- and alloimmune responses to the non-HLA antigen GSTT1, along with development of de novo (dn)HLA-DSAs, in a cohort of 146 pediatric non-sensitized recipients of first kidney allograft to analyze its role in ABMR and graft loss. Using a multiplex bead assay, we observed development of GSTT1 antibodies (Abs) in 71 recipients after transplantation, 16 with MFI >8031 (4th quartile: Q4 group). In univariate analyses, we found an association between Q4-GSTT1Abs and ABMR and graft loss, suggesting a potential role in inducing graft damage, as GSTT1 Abs were identified within ABMR biopsies of patients with graft function deterioration in the absence of concomitant intragraft HLA-DSAs. HLA-DSAs and GSTT1 Abs were independent predictors of graft loss in our cohort. As GSTT1 Ab development preceded or coincided with the appearance of dnHLA-DSAs, we tested and found that a model with the two combined parameters proved more fit to classify patients at risk of graft loss.